START: Overcoming Remaining Challenges - Elizabeth Zolotukhina (Journal of Strategic Security, 2009)
During the administrations of Presidents George W. Bush and VladimirPutin, the governments of Russia and the United States could not agreeon how to codify their balance of strategic offensive nuclear forces after the existing Strategic Arms Reductions Treaty (START) expired onDecember 5, 2009.1 The United States and Russia are currently engagedin negotiations to replace START with a new treaty before the end of this year.